2019
DOI: 10.1016/j.puhe.2018.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress among primary school teachers: a comparison with clinical and population samples

Abstract: The version presented here may differ from the published version. If citing, you are advised to consult the published version for pagination, volume/issue and date of publication Psychological distress amongst primary school teachers: a comparison with clinical and population samples

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 8 publications
2
24
1
1
Order By: Relevance
“…Furthermore, educational systems are guided by federal guidelines which are similar across regions, despite adaptations due to local characteristics being common. However, the results should not be extrapolated to the general population, since health related disorders of the teaching profession may not occur in the same magnitude 48 and as a consequence, medication consumption could be different.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, educational systems are guided by federal guidelines which are similar across regions, despite adaptations due to local characteristics being common. However, the results should not be extrapolated to the general population, since health related disorders of the teaching profession may not occur in the same magnitude 48 and as a consequence, medication consumption could be different.…”
Section: Discussionmentioning
confidence: 99%
“…Many teachers commented on the pressures they face, which may contribute to the shockingly high and sustained levels of psychological distress that we detected among teachers in this study; 10% scored above a cut-off point that suggests moderate depression at all four data points. 147 These high levels of stress and distress in the wider school environment may also have served to undermine any positive influence of TCM on self-efficacy, particularly in relation to the classroom management subscale, on which we did detect a statistically significant improvement in our uncontrolled feasibility work. 94 It may also be that our change to the short Teacher Self-Efficacy Scale in an effort to reduce participant burden rendered the measure insensitive, so future studies should consider using the original longer form 148 as we did in our feasibility work.…”
Section: Academic Attainmentmentioning
confidence: 73%
“…Titheradge et al . () demonstrated that a large percentage of teachers who participated in STARS had an EFQ score in the range indicative of moderate depression (EFQ 20 or above) at baseline (29%) and at follow‐up (20%).…”
Section: Discussionmentioning
confidence: 99%
“…Items are scored from 0 to 4 for items with distress content and from 4 to 0 for items with well‐being content. The EFQ has a maximum score of 40; a higher score indicates higher levels of distress with scores above 19 being indicative of at least moderate levels of clinical depression (Titheradge et al ., ). The mean ( SD ) score for a population‐representative sample of 2,109 professionals was 11.4 ( SD 5.9) (Green, McGinnity, Meltzer, Ford, & Goodman, ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation